disabled-1 Functions Cell Autonomously during Radial Migration and Cortical Layering of Pyramidal Neurons - Hammond, Vicki (J Neurosci, 2001)
Genetic mosaics offer an excellent opportunity to analyze complex gene functions. Chimeras consisting of mutant and wild-type cells provide not only the avenue for lineage-specific gene rescue but can also distinguish cell-autonomous from non-cell-autonomous gene functions. Using an independent genetic marker for wild-type cells, we constructed Dab1(+/+) ↔Dab1(−/−) chimeras with the aim of discovering whether or not the function of Dab1 during neuronal migration and cortical layering is cell autonomous.Dab1(+/+) cells were capable of radial migration and columnar formation in aDab1(−/−)environment. MostDab1(+/+) cells segregated to the superficial part of the mutant cortex, forming a multilayered supercortex. Neuronal birth-dating studies indicate that supercortex neurons were correctly layered, although adjacent mutant cortex neurons were in reversed order. Immunocytochemistry using Emx1, a marker for pyramidal neurons, indicates that the vast majority ofDab1(+/+) neurons in the supercortex were Emx1 immunoreactive. Confirmation of the pyramidal phenotype was demonstrated by the absence of GABA immunoreactivity amongDab1(+/+) cells in the supercortex. Myelin staining using 2′3′-cyclic nucleotide 3′-phosphodiesterase showed the supercortex was supported by a secondary white matter from which thick fiber tracts appear connected to the underlying mutant white matter. The presence ofDab1(+/+) cells failed to rescue inversion of cortical layers and the abnormal infiltration of the marginal zone by Dab1(−/−) cells. Conversely, mutant cells did not impose a mutant phenotype on adjacent wild-type neurons. These results suggest that Dab1 functions cell autonomously with respect to radial migration and cortical layering of pyramidal neurons.